PENINGKATAN KEMAMPUAN LITERASI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN DAN EFIKASI DIRI. - Samin Samin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
The ability of mathematical literacy is important in achieving mathematical learning outcomes. Reefikasi diriarch to learn the influence of learning models problems baefikasi dirid learning (PBL) To the students ' mathematic literacy skills, the self-efficacy influence on the enhancement of Students ' mathematical literacy skills, and the influence of the PBL and Efikasi dirilf Efficacy learning model interactions dengan the students ' mathematic literacy skills. The Sample for this reefikasi diriarch is 80 students from grade 9th of State Junior High School in South Jakarta. The study uefikasi diris a Likert scale to gain data about the dicipline and multiple choice questions to gather data about the increasing ability of mathematics literacy. Analysis data is used two-way analysis variance (ANOVA) with 2 x 2. We can conclude that there are: the influence of PBL type towards student mathematics literacy, an influence of self-efficacy towards student mathematics literacy, and the influence of interactions between the PBL learning model and self-efficacy towards student mathematics literacy. Therefore, the PBL and self-efficacy learning models can improve mathematical literacy skills, which can be used as math learning model in junior high school.